Strategi Guru PAI Dalam Meningkatkan Kedisiplinan Belajar Kelas X Jurusan Ilmu Pengetahuan Sosial Di MAN Batubara - Syahira, Nur (Fakultas Agama Islam, 2023)
This research raises the title of the PAI Teacher's Strategy in Improving Learning Discipline in Class The main moral is in learning discipline. This research aims to describe PAI Teachers' Strategies in Improving Learning Discipline in Class X, Social Sciences Department at MAN Batubara. This research is qualitative in nature. The subject of this research is Islamic religious education teachers. The object of this research is the strategies of Islamic religious education teachers in improving learning discipline. Research data was obtained through observation, interviews and documentation. The results of the research show that: 1) The learning discipline of students at Madrasah Aliyah Negeri Batubara is very less than optimal so that these students lack interest in participating in learning. Forms of indiscipline in learning by Madrasah Aliyah Negeri Batubara students include being noisy, not carrying out assignments given by teachers and others. Discipline in learning is very important because it can make students successful in the learning process and can create good learning conditions. 2) The driving factors for PAI teachers in improving student learning discipline are in the form of motivation, use of varied teaching methods, setting rules, student involvement and counseling. while inhibiting factors include student behavior problems that occur during the learning process, therefore teachers can be hampered in delivering learning in class. 3) Islamic religious education teachers' strategies for improving learning discipline include creating a conducive learning atmosphere, providing positive examples, conducting evaluations. and sanctions, and using fun learning methods and mental development.